2016
DOI: 10.1021/acs.cgd.6b00787
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Cut Method for the Quantification of Crystallization Kinetics. 1. Method Development

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…These experiments provide several combinations of temperature and supersaturation during one experiment and therefore an efficient investigation of the desired kinetics over the considered range of process conditions. The first part of this study [4] demonstrated the feasibility of a simple short-cut-method exploiting in silico data of a few seeded batch-crystallizations. This idea will be applied in the present study to three different substance systems, namely potassium aluminum sulphate dodecahydrate (KAL), potassium dihydrogen phosphate (KDP) and ortho aminobenzoic acid (oABA).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…These experiments provide several combinations of temperature and supersaturation during one experiment and therefore an efficient investigation of the desired kinetics over the considered range of process conditions. The first part of this study [4] demonstrated the feasibility of a simple short-cut-method exploiting in silico data of a few seeded batch-crystallizations. This idea will be applied in the present study to three different substance systems, namely potassium aluminum sulphate dodecahydrate (KAL), potassium dihydrogen phosphate (KDP) and ortho aminobenzoic acid (oABA).…”
Section: Introductionmentioning
confidence: 89%
“…The idea, which will be discussed in this contribution, is to use easily available experimental information about crystallization processes that can be acquired performing a few well planned cooling batch-experiments to quantify 1-dimensional crystallization kinetics [4]. The main task is therefore not to elucidate the underlying mechanism in detail but to provide sufficient information for a process design.…”
Section: Short-cut-methodsmentioning
confidence: 99%
See 3 more Smart Citations